Analisis Penggunaan Kata Disfemia pada Komentator Sepak Bola Liga Indonesia - Malik Maulana Ibrahim (Faculty of Economics, Law, and Humanities, 2020)
This paper aims to (1) describe the categories of forms of dysphemia use contained inIndonesian soccer commentators. (2) describe the taste value of dysphaemia contained inthe Indonesian soccer commentator. This research used qualitative descriptive method.The data in this study were the words of the Indonesian soccer league commentator.Subjects in this study were sentences containing words, phrases, and taste of dysphaemiain Indonesian soccer league commentators. The object of this study is the worddysphaemia in the soccer commentator Indonesia. The source of the data comes froma video recording of an Indonesian soccer league commentator. Techniques of datacollection used techniques to listen to Indonesian commentator of a football videorecording. The next technique used the technique of recording, the recorded technique isto record conversations of soccer commentators, and then researchers can easily identifythe forms of dysfemia contained in the soccer commentator Indonesia League that hasbeen recorded previously. The results reveals (1) The words (verbs, adjectives, and nouns)(2) in the form of phrases (verva phrase, adjective phrase, noun phrase) and (3) tastevalue (frightening, horrible, disgusting and scary) in the video recording.